Establishing a Europe-wide foundation for high quality midwifery education: The role of the European Midwives Association (EMA). (September 2018) - Vermeulen, Joeri; Luyben, Ans; Jokinen, Mervi; Matintupa, Eva; O'Connell, Rhona; Bick, Debra
Highlights: The freedom of movement of individuals is a cornerstone of European Union (EU) policy. European Directives on the recognition of professional qualifications for midwives informed a joint framework for quality midwifery education and practice in Europe. The European Midwives Association (EMA) has an important, ongoing role in establishing, securing and advancing high quality midwifery education and practice in EU member countries. Abstract: A cornerstone of European policy involves freedom of movement of individuals between member countries, which applies equally to those who use and provide maternity care. To promote and support safe, high quality maternity care, minimum standards for midwifery education and practice have been published, including Directives EEC/80/154 and EEC/80/155 which support the recognition of professional qualifications. These Directives established a minimum standard for midwifery education, including the duration and content of theoretical and practical education. Annex V of the Directives established a framework of professional activities to define and guide the scope of midwifery practice in EU member countries. The Directives were updated in 2013, with the European Midwives Association (EMA) an important partner in this process. While the degree of implementation of the Directives at individual country level varies, EMA has an ongoing role in ensuring, promoting and advancing high quality midwifery education and practice throughout the EU.